N,N-Bis(2-hdroxybenzylidene) phenylen-1,2-diamine - Kazak, C.; Arslan, N. B.; Genc, M.; Servi, S.; Buyukgungor, O. (Int Union Crystallography, 2006)
[Abstract Not Available]
Keywords: X-ray single-crystal diffraction; photochromic compounds; aromatic organic compounds